ISLAMIC BANK CUSTOMER LOYALTY: An Analysis of Griffin's Theory and Relevant Research - Rokhmat Subagiyo; Binti Mutafarida; Binti Nur Asiyah; Jusuf Bachtiar; Fauzan Fauzan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The study discusses the indicator of customer loyalty of Islamic banks according to Griffin's perspective and several relevant studies. The problems solved in this study are 1) what is the indicator of customer loyalty of Islamic banks according to Griffin? 2) what is the indicator of customer loyalty of Islamic banks according to some relevant studies? and 3) how is the comparison of Islamic bank customer loyalty indicators according to Griffin and other relevant studies? Based on the theoretical assumption, a customer is considered loyal if he/she makes regular purchase in a certain time interval. This study utilizes descriptive qualitative research with a library research approach. Deduction and comparative are done in analysis technique. Griffin’s theory focuses on behavioral and attitudinal approach. Meanwhile, other relevant research studies emphasize more on physical things, the availability of banking facilities and infrastructure. They also classified the loyalty into affective, conative, and action loyalty. There is a difference in Griffin’s theory and other studies, that customer loyalty is influenced by maqâsid al-sharî'ah. It means that the customer loyalty is determined by satisfactory level referring to sharia values.